Tinjauan Penyelenggaraan Pemilu Lokal Serentak Sebagai Upaya Mewujudkan Penyelenggaraan Pemerintahan Daerah Yang Lebih Baik - Melfa, Wendy; Idham, Idham (JUSTICIA SAINS - Jurnal Ilmu Hukum, 2025)
Filling the positions of existing regional government administrators requires two different elections. This at least displays different periods of office of the Regional Head and the Regional People's Representative Council, not focusing on local issues and solutions, election budget efficiency. These three things can be obstacles to building a better regional government. The problems in this study; 1) How is the law used as a means to realize a better regional government through the simultaneous filling of positions of regional government administrators? 2) Can the simultaneous filling of positions of regional government administrators in one simultaneous local election make a better regional government in perspective when juxtaposed with the filling of positions of regional government administrators through existing elections? This research method uses a literature study approach, concepts, and comparisons and by using the theory of law as a tool of social engineering (Roscoe Pond) it can be concluded that the law can be used as a means to design a better government through the renewal of the legal basis that is used as the legal basis for filling positions of regional government administrators through simultaneous local elections.